The Sheffield bone block procedure: a new operation for the treatment of glenoid bone loss in patients with anterior traumatic shoulder instability. Issue 2 (April 2016) - Venkatachalam, Santosh; Storey, Phil; Macinnes, Scott J; Ali, Amjid; Potter, David
Background: The purpose of the present study was to evaluate the results of the Sheffield bone block procedure for anteroinferior bone loss in traumatic shoulder instability. In this modified open technique, the medial half of coracoid process without its soft tissue attachments is used to provide congruent augmentation of the anteroinferior glenoid and secured with two screws. Methods: In this retrospective consecutive case series (2007–11), all patients having recurrent traumatic instability with glenoid bone loss > 20% and/or a large Hill–Sachs lesion were included. The shoulder function was evaluated clinically and by Oxford Shoulder Instability Score (OSIS; by post/telephone). Results: There were 84 patients in this series with a large proportion engaged in contact sports. Mean (range) age was 33 years (16 years to 45 years); male : female, 59 : 8; mean (range) follow-up period was 48 months (36 months to 84 months) and the response rate 89% (75/84). Mean postoperative OSIS was 43 (33 to 46) and one patient had re-dislocation (1.3%). No neurovascular complications/hardware failure/non-union/infections were noted. By 6 months, 85% patients had returned to pre-injury sport and 93% had returned to pre-injury work. Conclusions: The Sheffield bone block procedure provides reliable and satisfactory results in patients having recurrent instability with glenoid bone loss and/or a large Hill–Sachs lesion with minimal complications and an excellent chance of returning to original sport and occupation.